Effectiveness of Narrative Therapy in Addressing Psychological Challenges: A Systematic Review of Randomised Controlled Trials - Permatasari, Dyah Putri; Dwi Windarwati, Heni; Lestari, Retno (Indigenous: Jurnal Ilmiah Psikologi, 2026)
Background: Evidence on the effectiveness of Narrative Therapy remains limited and varies across age groups, psychological conditions, and cultural contexts; therefore, a systematic review is needed to integrate findings across studies for a more comprehensive understanding. Objective: This review aims to evaluate the effectiveness of Narrative Therapy in reducing psychological problems across all age groups based on evidence from previously published studies. Methods: A systematic review was conducted on 20 articles with Randomized Controlled Trial (RCT) designs obtained from major academic databases. Study selection was performed using strict inclusion and exclusion criteria. Research participants included children (≤17 years), adolescents (18–25 years), adults (26–59 years), and older adults (≥60 years) from various clinical and community settings across different countries. Results: Of the 20 studies analyzed, 18 showed significant results (p < 0.05) with moderate to large effect sizes (Cohen’s d = 0.5–1.6), while 2 studies were not significant. The highest recorded p-value was 0.019 and the highest t-value was −9.46 (p < 0.001). The greatest effectiveness was observed among children with anxiety and trauma survivors, along with improvements in self-efficacy, self-image, social relationships, and quality of life. Conclusion: Narrative Therapy is effective in reducing psychological symptoms such as depression, anxiety, PTSD, and loneliness, while enhancing self-efficacy, self-image, and quality of life across ages and cultures. The therapy is flexible, adaptive, and relevant for psychiatric nursing practice, making it a recommended evidence-based intervention in both clinical and community settings.